More than local adaptation: high diversity of response to seawater acidification in seven coral species from the same assemblage in French Polynesia. (16th June 2021) - Godefroid, Mathilde; Arçuby, Robin; Lacube, Yann; Espiau, Benoit; Dupont, Sam; Gazeau, Frédéric; Metian, Marc; Hédouin, Laetitia
Abstract: Responses of corals to seawater acidification have been extensively studied. Sensitivity varies widely between species, highlighting the need to avoid extrapolation from one to another to get an accurate understanding of coral community responses. We tested the responses of seven coral species ( Acropora cytherea, Acropora hyacinthus, Acropora pulchra, Leptastrea pruinosa, Montipora grisea, Pavona cactus, Pocillopora verrucosa ) from the Mo'orea lagoon to a 48-day exposure to three pH scenarios (pH 7.95, 7.7 and 7.3). Tissue necrosis, mortality, growth rates, photophysiological performances and colour index were recorded. Few significant differences were noted between pH 7.95 and 7.7, but species-specific responses were observed at pH 7.3. While our data do not allow identification of the mechanisms behind this diversity in response between species inhabiting the same environment, it can exclude several hypotheses such as local adaptation, skeletal type, corallum morphology or calcification rate as sole factors determining coral sensitivity to pH.